Motor development-focused exercise training enhances gross motor skills more effectively than ordinary physical activity in healthy preschool children: an updated meta-analysis - Xinchen Wang; Bo Zhou (Frontiers Media S.A., 2024)
PurposeThe growth of certain human brain structures peaks at early ages, and complex motor interventions could positively facilitate this process. This study aims to offer an updated meta-analysis regarding the effectiveness of motor development-focused exercise training on gross motor skills in preschool children.MethodsWe searched English- and Chinese-language electronic databases as of March 2024. The main eligibility criteria were as follows: participants were healthy children aged 3 to 6 years old, and the experimental design was a randomized controlled trial, with the control arm participating in either free play or ordinary physical education curriculum. We conducted a Hartung-Knapp random-effects meta-analysis of the standardized mean difference for locomotor, object control, or gross motor quotient.ResultsThe search identified 23 eligible studies, of which approximately 75% were considered to have a low risk of bias. Compared with active control, exercise training showed a large to very large effect size. Cohen's d values were 1.13, 1.55, and 1.53 for locomotor, object control, and gross motor quotient, respectively. From a probabilistic viewpoint, these effect sizes correspond to events that are "very likely to occur" and "almost sure to occur." Due to variations in intervention programs, all outcome measures showed high heterogeneity.ConclusionThis updated meta-analysis offers a realistic synthesis of the current evidence, leading to the conclusion that targeted motor skill exercise training can almost certainly enhance preschool children's gross motor skills. Practical implications are discussed regarding the refinement of the instructional framework and the dissemination of these findings in preschool settings.